Beetween Trust and Crisis: SCCT in Local Indonesian Beauty Brands Response Overclaim - Husniyah, Estri Khidmatul; Prasetyo, Bambang Dwi; Oktaviani, Fitri Hariana (Jurnal The Messenger, 2025)
Purpose: This study analyst the crisis communication strategies implemented by two major local Indonesian beauty brands, Azarine and The Originote, as both represent significant cases of overclaim crisis with a large digital audience base. The study primarily focuses on the application Situational Crisis Communication Theory (SCCT) to understand crisis communication responses chosen by each brand. Additionally, the study seeks to determine the effectiveness of this approach in maintaining public trust.   Methods: This study uses a descriptive quantitative approach with content analysis methods. Data was collected from official brand posts on Instagram and TikTok during the crisis period. Crisis communication strategies were classified based on the SCCT model. The coding process was carried out manually by two experts to ensure the accuracy of the categorization.   Findings: Azarine tends to minimize attribution of responsibility through a combination of denial, justification, compensation, and ingratiation. Meanwhile, The Originote emphasizes acknowledgment of mistakes and commitment to improvement through justification, compensation, ingratiation, and apology. The analysis results indicate that Azarine strategy is more effective in maintaining brand reputation stability and preserving public trust during the early stages of a crisis, while The Originote strategy has a greater impact on long-term image recovery through a more open and accommodating approach.   Originality: This study expands SCCT by applying to overclaim crises in the Indonesian beauty industry within the context of marketing communication. This context remains under-researched, and the study examines its implications for recovering public trust in digital environments.